Laboratory Testing Patterns by Day of Hospital Stay for Medical and Surgical Hospitalizations. (28th October 2021) - Brimhall, B; Whitted, M; Windham, A; Fernandez, J
Abstract: Introduction/Objective: Studies of laboratory test utilization and costs by specific hospital day of stay (DOS) have yet to be widely published. Evaluation of laboratory test use by DOS would be helpful to better predict laboratory test reduction as hospital length of stay (LOS) is shortened, since testing on the final day of hospitalization is likely to differ from the average daily figures. Methods/Case Report: Using an internal cost accounting database, we evaluated laboratory tests and costs by hospital DOS over one year (2017) at a large health system (N=133, 139 hospital days). To evaluate changes over the first days of hospitalization, we set day 1 of hospitalization as a baseline and determined subsequent days as a percentage of day 1 figures. We also calculated laboratory variable cost as a percent of aggregate variable costs per DOS. We limited our analysis to the first week of hospitalization. We employed Medicare Severity Diagnosis Related Groups (MSDRG), used by the US Centers for Medicare and Medicaid Services (CMS), to aggregate hospital encounters into medical or surgical hospitalizations using MSDRG grouping methods. Results (if a Case Study enter NA): For medical inpatient stays, average laboratory tests (variable costs) were 10.8 ($74.11) on day 1, 7.7 ($38.53) on day 2, and 5.8 ($23.75) on day 3, with little change over the next four hospital DOS. Laboratory testing, as a percent of day 1 testing, for days 2-7 was: 70.7%, 53.4%, 54.3%, 54.5%, 55.1%, and 54.0%. Laboratory variable costs represented 7.8% of aggregate variable costs on hospital day 1 and declined sequentially over days 2-7: 5.6%, 4.3%, 3.9%, 3.8%, 3.8%, and 3.5%. For surgical hospitalizations, average laboratory tests (variable costs) were 18.2 ($130.02) on day 1, 11.9 ($57.38) on day 2, and 8.4 ($35.32) on day 3. As with medical stays, there was little change over the next four hospital DOS. Laboratory testing, as a percent of day 1 testing, for days 2-7 was: 65.6%, 46.1%, 44.6%, 46.3%, 45.9%, and 44.9%. Laboratory variable costs represented 3.2% of aggregate variable costs on hospital day 1 and remained essentially unchanged over the following days (range 3.3%-3.7%). Conclusion: Laboratory variable costs are highest on the first day of hospitalization and decline over subsequent days to flatten by day 3.